When diving animals help us to observe the oceans: the MEOP data portal - Roquet, Fabien; Boehme, Lars; Bester, Marthán N.; Bornemann, Horst; Brasseur, Sophie; Charrassin, Jean-Benoit; Costa, Dan; Fedak, Mike A.; Guinet, Christophe; Hall, Alisa; Harcort, Rob; Hindell, Mark A.; et al. (2016)
Seals help gather information on some of the harshest environments on the planet, through the use of miniaturized ocean sensors glued on their fur. The resulting data – gathered from remote, icy seas over the last decade – are now freely available to scientists around the world from the data portal http://www.meop.net. The Polar oceans are changing rapidly as a result of global warming. Ice caps in Antarctica and Greenland are melting, releasing large quantities of freshwater into surface waters. The winter sea ice cover is receding in the Arctic and in large areas of the Southern Ocean, which promotes further warming. Southern winds are intensifying for reasons that are not fully understood. To understand the changing marine environment, it is necessary to have a comprehensive network of oceanographic measurements. Yet, until recently, the harsh climate and remoteness of these areas make them extremely difficult to observe. Diving marine animals equipped with sensors are now increasingly filling in the gaps. When diving animals help us to observe the oceans Since 2004, hundreds of diving marine animals, mainly Antarctic and Arctic seals, were fitted with a new generation of Argos tags developed by the Sea Mammal Research Unit of the University of St. Andrews in Scotland (Fig. 1). These tags can be used to investigate simultaneously the at-sea ecology (displacement, behaviour, dives, foraging success.) of these animals while collecting valuable oceanographic data (Boehme et al. 2009). Some of these species are travelling thousands of kilometres continuously diving to great depths (590 ± 200 m, with maxima around 2000m). The overall objective of most marine animal studies is to assess how their foraging behavior responds to oceanographic changes and how it affects their ability to aquire the resources they need to survive. But in the last decade, these animals have become an essential source of temperature and salinity profiles, especially for the polar oceans. For example, elephant seals and Weddell seals have ...